1996
DOI: 10.1159/000121135
|View full text |Cite
|
Sign up to set email alerts
|

Subdental Synchondrosis Fracture in Children: The Value of 3-Dimensional Computerized Tomography

Abstract: A case is presented illustrating the usefulness of computerized tomography (CT) with 3-dimensional (3-D) reconstruction for evaluation of a subdental synchondrosis fracture in a child. Odontoid fractures in children less than 7 years of age occur at the subdental synchondrosis and are typically diagnosed with plain x-rays. However, a delay in diagnosis is common as these injuries may not be appreciated on initial roentgenographic evaluation. The authors present a case of a 2-year-old boy with a subdental synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…9 We have found that MR imaging can help in equivocal cases; a high signal at the synchondrosis and soft-tissue changes at the C1-2 level provide convincing evidence of a synchondrosis fracture (Fig. 2C).…”
Section: Discussionmentioning
confidence: 77%
“…9 We have found that MR imaging can help in equivocal cases; a high signal at the synchondrosis and soft-tissue changes at the C1-2 level provide convincing evidence of a synchondrosis fracture (Fig. 2C).…”
Section: Discussionmentioning
confidence: 77%
“…Consecutively, these findings have been confirmed by a number of researchers [1,2,7,10,11,13]. Since these early observations it has been generally accepted that the subdental synchondrosis is a bipolar growth zone that contributes to the overall heights of the basis of the dens as well as of the vertebral body, and that it is consistently located below the level of C1-C2 articulation.…”
mentioning
confidence: 71%
“…The cartilaginous end plate between the dens and the body of C2 does not ossify until the child is 5 to 7 years old5,15). Therefore, odontoid synchondrosis fractures are common in young children less than 7 years of age3,5,6,10,11,14,15). Conventionally, the first line of treatment for odontoid synchondrosis fractures in children is immobilization in a halo vest3,6).…”
Section: Introductionmentioning
confidence: 99%